Literature Review: IT, Human Resource, and Organizational Factors in Electronic Medical Record Implementation: Literature Review: Faktor IT, SDM, dan Organisasi dalam penerapan Rekam Medis Elektronik - Nur Sulistyani, Putri; Naziha, Nada; Faturrafi, Nandana; Restiani Yuliawati, Nura; Fauziah Priyani, Rani (Jurnal Rekam Medis dan Informasi Kesehatan, 2025)
The rapid growth of digital health systems has encouraged hospitals and primary care centers to adopt Electronic Medical Records (EMR) as a more efficient and protected method of managing patient information. This review aims to identify the key elements that shape the success of EMR implementation, focusing on technological, human resource, and organizational aspects. A literature review was conducted using ten studies published between 2021 and 2025. The findings indicate that system reliability, data protection, and user-friendly features strongly support EMR adoption. From the human resource perspective, staff readiness and consistent training play a crucial role in system acceptance. At the organizational level, leadership involvement, a work culture that welcomes innovation, and adequate infrastructure become essential drivers. Common challenges still encountered include limited IT support, the absence of system integration across units, and interfaces that remain difficult to navigate. Overall, EMR implementation thrives when technological capacity, human competence, and organizational commitment work in alignment. The review is expected to provide insights for developing more effective and sustainable EMR implementation strategies.